Spiritual education module for out-of-wedlock pregnant adolescents - Md Sham F.; Dakir J.; Tibek S.R.H.; Awal N.A.M.; Hamjah S.H.; Ismail A.H.; Ismail M.; Ismail Ibrahim S.M. (Sakarya University, 2024)
Indexed by SCOPUS